EFEKTIVITAS TEKNIK MENYENDAWAKAN DALAM MENGURANGI GUMOH PADA BAYI: STUDI KASUS DI PMB Bdn. Silvi Ayu, S.Keb PEKANBARU - Cindy Amelia; Lita Nafratilova (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
Spit-up in babies is a common condition due to an immature digestive system. One effort that can be done to reduce spit-up in infants is the burping technique after breastfeeding. This study aims to determine the effectiveness of the burping technique in reducing spit-up in Mrs. Y's baby at PMB Bdn. Silvi Ayu, S. Keb Pekanbaru. The method used is a case study with the intervention provided in the form of a burping technique after each breastfeeding session. The results showed a decrease in the frequency of spit-up after the intervention was carried out regularly.